2015
DOI: 10.1242/jcs.158964
|View full text |Cite
|
Sign up to set email alerts
|

Bit-1 is an essential regulator of myogenic differentiation

Abstract: Muscle differentiation requires a complex signaling cascade that leads to the production of multinucleated myofibers. Genes regulating the intrinsic mitochondrial apoptotic pathway also function in controlling cell differentiation. How such signaling pathways are regulated during differentiation is not fully understood. Bit-1 (also known as PTRH2) mutations in humans cause infantile-onset multisystem disease with muscle weakness. We demonstrate here that Bit-1 controls skeletal myogenesis through a caspase-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Here, Fernando et al [ 29 ] demonstrated that transient caspase-3 activity is required for myoblast differentiation and that this non-death activity is mediated in part through the cleavage activation of the Ste-20 like kinase, macrophage stimulating 1 (MST1). Subsequent studies have established that the key elements of the intrinsic mediated cell death pathway are fully conserved to engage caspase 3 during myoblast differentiation [ 37 , 77 ]. Once activated, caspase 3 targets multiple substrates to engage the differentiation program (Fig.…”
Section: Caspase-mediated Proteolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Here, Fernando et al [ 29 ] demonstrated that transient caspase-3 activity is required for myoblast differentiation and that this non-death activity is mediated in part through the cleavage activation of the Ste-20 like kinase, macrophage stimulating 1 (MST1). Subsequent studies have established that the key elements of the intrinsic mediated cell death pathway are fully conserved to engage caspase 3 during myoblast differentiation [ 37 , 77 ]. Once activated, caspase 3 targets multiple substrates to engage the differentiation program (Fig.…”
Section: Caspase-mediated Proteolysismentioning
confidence: 99%
“…These observations confirm that caspase 3 acts at multiple points to secure the differentiation program, yet the mechanism that spurs caspase activity at these specific temporal junctures remains unknown. Satellite cell activation has been reported to trigger engagement of the extrinsic mediated cell death pathway such as the Fas-associated protein with death domain (FADD) receptor [ 14 ], yet the requisite initiator caspase for this pathway, caspase 8, does not appear to be appreciably activated at this stage [ 37 ]. Given the central role of caspase 3 signaling in the differentiation process, there is a significant need to identify (1) the pathways that engage the activation of this protease, (2) the full range of substrates that facilitate its capacity to induce differentiation, and (3) the mechanisms that restrain protease activity and direct it to a non-death cell function.…”
Section: Caspase-mediated Proteolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ptrh2-null myoblasts exhibit earlier and higher expression levels of troponin T, myosin-2, and myogenin compared to age-matched controls, suggesting premature differentiation occurs when PTRH2 protein is absent. Reexpression of PTRH2 in null myoblasts rescues early differentiation and decreases caspase activity similar to littermate age-matched controls 44 .…”
Section: Ptrh2 Regulates Myogenic Differentiation and Maintains Skelementioning
confidence: 66%
“…Overall, it was concluded that the UBL‐UBA shuttling pathway in the ubiquitin‐proteasome pathway is negatively regulated by PTRH2 (Ishii, Funakoshi, & Kobayashi, ). Notably, in mammalian cells, two additional functions of PTRH2 were reported: (1) Promoting cell survival via activation of both the PI3K‐AKT‐NFkB pathway and of Bcl‐2 transcription (Griffiths et al, , ); and (2) Promoting cell death by induction of anoikis (cell death induced upon cell detachment) (Kairouz‐Wahbe et al, ), which requires release of the protein from mitochondria and formation of a complex with the transcriptional regulator amino‐terminal enhancer of split (AES). Thus, PTRH2 is a multifunctional protein that participates in various cellular functions in various locations in the cell (Jan et al, ).…”
Section: Introductionmentioning
confidence: 99%